78. Diagnostic accuracy of neurophysiological tests (EEG and SEP) in comatose patients after cardiac arrest: Protocol presentation of Italian Multicentric Study (ProNeCA). Issue 4 (April 2016) - Amantini, A.; Audenino, D.; Callegarini, C.; Carrai, R.; Celani, M.G.; Di Capua, M.; Donato, F.; Foresti, C.; Lanteri, P.; Lombardi, M.; Madera, L.; Marelli, A.; et al.
Abstract : The prediction of neurologic outcome in comatose patients after cardiac arrest (CA) has been investigated and the findings were summarized in a practice parameter of the American Academy of Neurology (1). These guidelines did not include the EEG as a reliable outcome indicator but recent studies on continuous EEG recorded during TH have re-evaluated the role of EEG (2–4). These studies underline the utility of a simplified classification system of EEG patterns and point to which pattern attains reliable predictive value both for good and bad outcomes. These reports are of high clinical relevance because, until today, the possibility of identifying early prognostic indicators of good outcome in patients surviving to CA has not been investigated. At the best of our knowledge, only few multicentre prospective studies (4–6) analyzed the prognostic value of EEG and SEP recorded in the same patient after CA as single predictor but none analyzed the diagnostic accuracy of the association of these two tests. We present the study protocol of Italian Multicentre Study about prognostic value of EEG and SEP in comatose patients after CA (ProNeCA) proposed by study group of "Intraoperative and Intensive Care Clinical Neurophysiology" of the Italian Society of Clinical Neurophysiology.